Conference Report: Paradigmes et perspectives de la littérature médiévale comparée | Paradigmen und Perspektiven einer Mediävistischen Komparatistik | Paradigms and Perspectives of a Comparative Medieval Literature (Fribourg Colloquium 2021) (Interfaces: A Journal of Medieval European Literatures, 2022)
Conference Report of the Fribourg Colloquium 2021 Paradigms and Perspectives of a Comparative Medieval Literature (8-10 September 2021), organised by medieval literature scholars of the Institut d’études médiévales at the University of Fribourg (Switzerland).
Keywords: comparative literature; medieval literature; comparative medieval literature; Fribourg Colloquium; Europe